Impact Adaptability Strength of Arm and Self-Trust in Forward Roll Proficiency among Vocational High School Students at State 2 Makassar - Basith, Andi Yulianti; Ichsani, Ichsani (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. This research is to determine: (1) the influence of flexibility on self-confidence in students at State Vocational School 2 Makassar, (2) the influence of arm strength on self-confidence in students at State Vocational School 2 Makassar, (3) the influence of flexibility on forward roll ability in students at State Vocational School 2 Makassar, (4) the influence of arm strength on forward roll ability in students at State Vocational School 2 Makassar, (5) the influence of self-confidence on forward roll ability in students at State Vocational School 2 Makassar. Materials and Methods. This research is a descriptive research. The population of this research is all students of SMK Negeri 2 Makassar, the research sample is 30 people. The sampling technique is by random sampling technique. Data analysis used is path analysis ( Path Analysis ). Using SPSS 20 with a significance level of α = 0.05. Results. this study include descriptive research. The population of this study is all vocational high school students. State Vocational High School 2 Makassar, the research sample consisted of 30 people. The sampling technique was random sampling. The data analysis used was path analysis. Using SPSS 20 with a significance level of α = 0.05. Based on the results of the data analysis, this study concluded that; (1) there is a significant influence of flexibility on self-confidence in students of State Vocational High School 2 Makassar p = 0.334 (PValue 0.05); (2) there is a significant influence of arm strength on self-confidence in students of State Vocational High School 2 Makassar with a p value of = 0.270 (PValue 0.05); (3) there is a significant influence of flexibility on the ability to roll forward in students of State Vocational High School 2 Makassar with a p value of = 0.417 (PValue 0.05); (4) there is a significant influence of arm strength on the ability to roll forward in students of State Vocational School 2 Makassar with a p value of = 0.291 (PValue 0.05); (5) there is a significant influence of self-confidence on the ability to roll forward in students of State Vocational School 2 Makassar with a p value of = 0.335 (PValue 0.05). Conclusion. The implementation of poison ball warm-up has demonstrated efficacy in enhancing students' engagement in the sport of volleyball. The study's results indicated a substantial enhancement in interest, active engagement, and fundamental volleyball skills following the implementation of this warm-up technique